Vertical Transfer Success - Valerie O. Paton (Journal of College Orientation, Transition, and Retention, 2015)
The authors conducted a qualitative investigation of Hispanic students’ perceptions of the experience of vertical transfer from community college to a four-year institution. The study participants were students who had completed vertical transfer from two community colleges into a four-year degree program co-located in a region of the southwestern United States. Participants were predominantly Hispanic, male, and first generation. The findings of focus group sessions and survey data are analyzed and capture participants’ perceptions of issues that are essential to transfer success at the pre-, mid-, and post-transfer phases of the transition process and post-graduation goals and expectations.